Phosphoenolpyruvate:carbohydrate phosphotransferase systems of bacteria - Postma, P W; Lengeler, J W; Jacobson, G R (Microbiological reviews, 1993)
Numerous gram-negative and gram-positive bacteria take up carbohydrates through the phosphoenolpyruvate (PEP):carbohydrate phosphotransferase system (PTS). This system transports and phosphorylates carbohydrates at the expense of PEP and is the subject of this review. The PTS consists of two general proteins, enzyme I and HPr, and a number of carbohydrate-specific enzymes, the enzymes II. PTS proteins are phosphoproteins in which the phospho group is attached to either a histidine residue or, in a number of cases, a cysteine residue. After phosphorylation of enzyme I by PEP, the phospho group is transferred to HPr. The enzymes II are required for the transport of the carbohydrates across the membrane and the transfer of the phospho group from phospho-HPr to the carbohydrates. Biochemical, structural, and molecular genetic studies have shown that the various enzymes II have the same basic structure. Each enzyme II consists of domains for specific functions, e.g., binding of the carbohydrate or phosphorylation. Each enzyme II complex can consist of one to four different polypeptides. The enzymes II can be placed into at least four classes on the basis of sequence similarity. The genetics of the PTS is complex, and the expression of PTS proteins is intricately regulated because of the central roles of these proteins in nutrient acquisition. In addition to classical induction-repression mechanisms involving repressor and activator proteins, other types of regulation, such as antitermination, have been observed in some PTSs. Apart from their role in carbohydrate transport, PTS proteins are involved in chemotaxis toward PTS carbohydrates. Furthermore, the IIAGlc protein, part of the glucose-specific PTS, is a central regulatory protein which in its nonphosphorylated form can bind to and inhibit several non-PTS uptake systems and thus prevent entry of inducers. In its phosphorylated form, P-IIAGlc is involved in the activation of adenylate cyclase and thus in the regulation of gene expression. By sensing the presence of PTS carbohydrates in the medium and adjusting the phosphorylation state of IIAGlc, cells can adapt quickly to changing conditions in the environment. In gram-positive bacteria, it has been demonstrated that HPr can be phosphorylated by ATP on a serine residue and this modification may perform a regulatory function.